The Islamic Republic of Mauritania : Detailed Assessment Report Anti-Money Laundering and Combating the Financing of Terrorism - World Bank (World Bank, Washington, DC, 2021)
Mauritania is a vast African country, two-thirds of whose territory is covered by desert. It borders four countries (Morocco, Algeria, Mali, and Senegal), and derives most of its revenue from the extraction of iron ore from deposits located in the northern part of the country. The discovery of sizable petroleum deposits, which began to be extracted in 2006, will probably have a significant impact on the country's future economic growth, which registered 5 percent in 2005. Mauritania also has significant gold and diamond reserves, for which several exploration permits have been issued. This report draws on information gathered in the course of discussions with representatives of the public sector and the private financial sector (banks, savings institutions, insurance) and private nonfinancial sector (notaries, lawyers and NGOs).